2016
DOI: 10.1111/1365-2435.12701
|View full text |Cite
|
Sign up to set email alerts
|

Parasite infection and decreased thermal tolerance: impact of proliferative kidney disease on a wild salmonid fish in the context of climate change

Abstract: Summary Parasites and pathogens can have an important effect on their host's thermal resistance. The impact of parasite infection on host physiological performances has traditionally been studied in controlled laboratory conditions, and much less is known about its actual effects in wild populations. Nonetheless, such knowledge is critical when assessing the effect of climate change on the future survival of the host. Tetracapsuloides bryosalmonae is a myxozoan endoparasite causing proliferative kidney disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 64 publications
(110 reference statements)
1
112
0
Order By: Relevance
“…Comparison of the renal swelling of the 6 samples with the earlier data from anadromous brown trout collected from Estonia (River Vainupea, Bruneaux et al 2017) indicated that some individuals from the River Siuntionjoki exhibited severe signs of PKDinduced kidney hyperplasia (K:B ratio > 0.3; Fig. 2).…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…Comparison of the renal swelling of the 6 samples with the earlier data from anadromous brown trout collected from Estonia (River Vainupea, Bruneaux et al 2017) indicated that some individuals from the River Siuntionjoki exhibited severe signs of PKDinduced kidney hyperplasia (K:B ratio > 0.3; Fig. 2).…”
Section: Resultsmentioning
confidence: 61%
“…Before storing the sample in 96% ethanol, the body section was photo graphed with a digital camera for measurement of the kidney-to-body thickness ratio (K:B ratio, as in Fig. 1a in Bruneaux et al 2017) the PKD-induced hyperplasia of the kidney. We compared the estimated kidney hyperplasia measurements (K:B ratio) to published data on T. bryo sal monae-infected 0+ brown trout (n = 77) collected from the River Vainupea, Estonia (Bruneaux et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations